2009
DOI: 10.1073/pnas.0904506106
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule agonists for the thyrotropin receptor stimulate thyroid function in human thyrocytes and mice

Abstract: Seven-transmembrane-spanning receptors (7TMRs) are prominent drug targets. However, small-molecule ligands for 7-transmembrane-spanning receptors for which the natural ligands are large, heterodimeric glycoprotein hormones, like thyroid-stimulating hormone (TSH; thyrotropin), have only recently been reported, and none are approved for human use. We have used quantitative high-throughput screening to identify a small-molecule TSH receptor (TSHR) agonist that was modified to produce a second agonist with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 46 publications
5
113
2
Order By: Relevance
“…We determined whether other TSHR agonists-a small- (Neumann et al, 2009) and a thyroid-stimulating antibody M22 (Sanders et al, 2004)-would cause persistent signaling. We used maximally effective doses of C2 and M22 as determined previously (Sanders et al, 2004;Neumann et al, 2009) and showed that they were maximally effective because the two doses gave similar levels of stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We determined whether other TSHR agonists-a small- (Neumann et al, 2009) and a thyroid-stimulating antibody M22 (Sanders et al, 2004)-would cause persistent signaling. We used maximally effective doses of C2 and M22 as determined previously (Sanders et al, 2004;Neumann et al, 2009) and showed that they were maximally effective because the two doses gave similar levels of stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…We used maximally effective doses of C2 and M22 as determined previously (Sanders et al, 2004;Neumann et al, 2009) and showed that they were maximally effective because the two doses gave similar levels of stimulation. We found qualitatively similar effects of C2 and M22 on persistent cAMP and IP1 signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interhelical network of hydrogen bond between Leu-457, Asp-578, and Asn-619 has been shown to be highly conserved in all the three GpHR members as shown through the rearrangement of carboxylate oxygen of TSHR N674 (Asn-619 in LHR) with Asp-633 (Asp-578 in LHR), resulting in a switch between the activated and inactivated states (29). Control of such an interhelical molecular switch by modulating the ECLs has already been exploited in designing small molecule agonist for TSHR and LHR (19). The above data taken together would suggest that antibody or small molecules binding to ECLs or the exoplasmic face of the TMH can affect global TMD conformation.…”
Section: Spatial Organization Of the Loops In The Resting And Hormonementioning
confidence: 99%
“…[9][10][11][12][13] TSHr can specifically bind the thyroid-stimulating hormone (TSH). This specific binding behavior of TSHr with TSH can be adapted for generating a nanoparticle (NP) drug-delivery system to target thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%